The Role of Content Marketing and Customer Experience in Increasing Customer Loyalty in the Beauty Industry in Jakarta - Rosdiana Rosdiana; Rani Eka Arini; Stevanus Johan Gomies (West Science Social and Humanities Studies, 2024)
This study explores the role of content marketing and customer experience in enhancing customer loyalty within the beauty industry in Jakarta. Utilizing a quantitative approach, data were collected from 180 customers through a structured questionnaire employing a Likert scale ranging from 1 to 5. The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to determine the relationships and i0mpact of content marketing and customer experience on customer loyalty. The results indicate a significant positive correlation between content marketing and customer experience, both of which substantially contribute to increased customer loyalty. This study highlights the importance of strategic content marketing and exceptional customer experience in fostering customer loyalty, providing valuable insights for practitioners and marketers in the beauty industry.